2020
DOI: 10.30657/pea.2020.26.16
|View full text |Cite
|
Sign up to set email alerts
|

Tribological behavior of low-alloyed steel after nitriding

Abstract: The tribological properties of the nitride layer applied to the low-alloyed steel were investigated in this research. Experimental work included determination if the chemical composition, wear resistance, Rockwell, Vickers and nano-indentation tests, both of the substrate material – the low-alloyed steel and the deposited nitride layer. From the results obtained in those experiments authors concluded that applying the nitride layer does not significantly improve the tribological properties of the tested lowall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Vicen et al [ 22 ] investigated the tribological properties of a nitride layer applied to a low-alloyed steel. The authors reported the results of the experimental work, which included determination of the chemical composition and wear resistance, and Rockwell, Vickers and nano-indentation tests, both of the substrate material—the low-alloyed steel—and the deposited nitride layer.…”
Section: Introductionmentioning
confidence: 99%
“…Vicen et al [ 22 ] investigated the tribological properties of a nitride layer applied to a low-alloyed steel. The authors reported the results of the experimental work, which included determination of the chemical composition and wear resistance, and Rockwell, Vickers and nano-indentation tests, both of the substrate material—the low-alloyed steel—and the deposited nitride layer.…”
Section: Introductionmentioning
confidence: 99%
“…The tribological investigation was performed on model samples, prepared from the hard-faced surfaces, on a tribometer by the “block-on-disc” method, similar to some previous testing [ 30 , 31 ]. The samples were prepared in such a way to simulate the operation conditions of teeth of the coupled gears.…”
Section: Tribological Metallurgical and Hardness Investigationsmentioning
confidence: 99%
“…Their conclusion was that the low-precision gear profile grade reduces the ability to detect faults, while the gears with high quality teeth surfaces allowed for detecting the smaller faults. (Vicen et al, 2020) investigated the tribological properties of a nitride layer applied to a low-alloyed steel. The authors' experimental work included determination of the chemical composition and wear resistance, as well as the Rockwell, Vickers and nano-indentation tests, both of the substrate material and the deposited layer.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Authors of this article have some experience on this subject (Lazić et al, 2009;Lazić et al, 2014;Lazić et al, 2016;Arsić et al, 2016a;Arsić et al, 2016b) and have pointed to possibility of using the reparation for restoring the damaged parts of various machine systems. Based on investigated literature one can conclude that a small number of researchers were considering influence of the regeneration procedure on tribological characteristics of regenerated gears, especially from the point of view of technological inheritance (Vicen et al, 2020). Various hard-facing methods and their application in the repara-tion process of gears were considered in authors' own investigations (Markovic et al, 2011;Markovic et al, 2013;Markovic et al, 2021), where results of experimental metallurgical investigations of the repaired gear teeth were analyzed (Mohammed et al, 2020;Vasić et al, 2020).…”
Section: Introductionmentioning
confidence: 99%